The adenylosuccinate synthetase‐1 gene is activated in the hypertrophied heart - Wen, H. Y. (J Cell Mol Med, 2007)
Adenylosuccinate synthetase 1 (ADSS1) functions as an important component in adenine nucleotide biosynthesis and is abundant in the heart. Here we report that the Adssl gene is up‐regulated in two in vivo rodent models of surgically induced cardiac hypertrophy. In addition, we examined an in vitro hypertrophy system of rat neonatal cardiomyocytes treated with angiotensin II to study Adssl gene regulation. We show that this stimulus triggers a signaling cascade that results in the activation of the Adssl gene. The induction of Adssl gene expression was blocked by cyclosporin A in vitro, suggesting that calcineurin, a calmodulin activated phosphatase, is involved in this signaling pathway. Consistent with this view we provide evidence that the induction of Adss1 by angiotension II requires the presence of an NFAT binding site located 556 base pairs upstream of the Adssl transcription start site. We propose that ADSS1 plays a role in the development of cardiac hypertrophy through its function in adenine nucleotide biosynthesis.